Creating oscillons and oscillating kinks in two scalar field theories - Correa, R. A.C.; De Souza Dutra, A. [UNESP]; Frederico, T.; Malomed, Boris A.; Oliveira, O.; Sawado, N. (AIP Publishing, 2019)
Oscillons are time-dependent, localized in space, extremely long-lived states in nonlinear scalar-field models, while kinks are topological solitons in one spatial dimension. In the present work, we show new classes of oscillons and oscillating kinks in a system of two nonlinearly coupled scalar fields in 1 + 1 spatiotemporal dimensions. The solutions contain a control parameter, the variation of which produces oscillons and kinks with a flat-top shape. The model finds applications in condensed matter, cosmology, and high-energy physics.